Normal Variants, Pitfalls, and Artifacts in Ga-68 Prostate Specific Membrane Antigen (PSMA) PET/CT Imaging - Malan, Nico; Vangu, Mboyo-di-Tamba (Frontiers in Nuclear Medicine, 2022)
The advent of gallium 68 prostate specific membrane antigen (PSMA) PET imaging has revolutionized the diagnosis and treatment of prostate cancer. PSMA is a transmembrane glycoprotein that is overexpressed in prostate cancer and yields images with high tumour-to-background contrast. Effective “one-stop-shop” imaging of the prostate, lymph nodes, soft tissue and bone is achieved with PSMA PET. Compared to conventional imaging, PSMA PET provides superior sensitivity and specificity and plays a pivotal role in staging high-risk prostate cancer as well as in biochemical recurrence by identifying oligometastatic disease. PSMA PET furthermore assists in the selection of patients with metastatic castrate resistant prostate cancer for possible treatment (e.g., labelled with a beta emitter lutetium 177) by using a theranostic approach. The term “prostate specific” is a misnomer as PSMA is also present in other malignant and benign conditions since it acts as a folate hydrolase. To avoid pitfalls and false-positives, a sound knowledge of the normal biodistribution of PSMA as well as other potential causes for false-positive uptake is imperative. This review will describe the expected patterns of distribution of Ga 68 PSMA PET imaging and the common pitfalls noted in published literature since the topic is still evolving.